2019
DOI: 10.1002/chem.201900168
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Diastereoselective Arylogous Michael Addition of Unactivated Phthalides

Abstract: The first highly enantioselective arylogous Michael reaction (AMR) of 3‐unsubstituted phthalides has been described. This phase‐transfer methodology, which uses catalytic amounts of KOH/18‐crown‐6 catalyst in mesitylene in the presence of N,O‐bis(trimethylsilyl)acetamide (BSA), gives access to a broad range of 3‐monosubstituted phthalides with high levels of syn diastereoselectivity and good yields, starting from 3‐unsubstituted derivatives and diverse α,β‐unsaturated carbonyl compounds. The reaction also appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
3
4
0
Order By: Relevance
“…Since the space above and below the positively charged K + ⊂ 18-crown-6 ether is easily accessible, we proposed a very tight ion pair with these macrocycles, provided that a low dielectric constant solvent is used. DFT calculations of such contact ion pair, in which both the dienolate anion and the carbonyl group of the α,β-unsaturated ketone are coordinated to K + , demonstrated a strong preference for the exo-type approach, leading to the syn adduct (Figure 2a), in agreement with the experimental results [59,60]. On the other hand, we suggested that catalytic quaternary ammonium salts, 15-crown-5 derivatives, and [2,2,2]-cryptand, entail separated ion pairs, as a result of the hard accessibility of positive charge for R 4 N + , the sandwich K + ⊂ (15-crown-5) 2 , and the cryptate K + ⊂ [2,2,2]-crypt.…”
Section: γ-Butenolides and 2-pyrrolinonessupporting
confidence: 84%
See 1 more Smart Citation
“…Since the space above and below the positively charged K + ⊂ 18-crown-6 ether is easily accessible, we proposed a very tight ion pair with these macrocycles, provided that a low dielectric constant solvent is used. DFT calculations of such contact ion pair, in which both the dienolate anion and the carbonyl group of the α,β-unsaturated ketone are coordinated to K + , demonstrated a strong preference for the exo-type approach, leading to the syn adduct (Figure 2a), in agreement with the experimental results [59,60]. On the other hand, we suggested that catalytic quaternary ammonium salts, 15-crown-5 derivatives, and [2,2,2]-cryptand, entail separated ion pairs, as a result of the hard accessibility of positive charge for R 4 N + , the sandwich K + ⊂ (15-crown-5) 2 , and the cryptate K + ⊂ [2,2,2]-crypt.…”
Section: γ-Butenolides and 2-pyrrolinonessupporting
confidence: 84%
“…Consequently, under those conditions, we suggested that the cation chelation effect no longer occurs, and the dienolate anion reacts as a "naked" nucleophile. DFT calculations of the reaction transition state between the "naked" dienolate and α,β-unsaturated ketone revealed a preference for the endo-type approach, leading to the anti-adduct, that was again in agreement with the experimental results (Figure 2b) [59,60]. An asymmetric direct vinylogous aldol reaction of (5H)-furan-2-ones catalyzed by in situ generated cinchona alkaloids derived 4-methoxy-phenoxide salts was also reported [61].…”
Section: γ-Butenolides and 2-pyrrolinonessupporting
confidence: 78%
“…No conversion was observed under the above‐mentioned reaction conditions. To our pleasure, as reported in our previous studies, [11] the addition of stoichiometric amounts of the silylating agent BSA enabled smooth conversion to the desired adduct even at −20 °C, in good yield and diastereopure form. Interestingly, X‐ray diffraction analysis revealed the opposite diastereoselection, with exclusive formation of Syn‐Re ‐ 3 ia product [12]…”
Section: Resultssupporting
confidence: 59%
“…[12] Basing on our previous mechanistic calculations, the Si-selectivity observed with the NaOH/DCH18C6 catalytic system in toluene can be rationalized assuming coordination of both the Michael acceptor's carbonyl groups to the metal cation in the transition state. [11] As a result, the conformation of alkene acceptor is blocked into a syn-periplanar arrangement of the carbonyl groups, causing the oxazolidinone's phenyl ring to shield the Re-face (Figure 2A). This hypothesis is in accordance with the stereoselectivity reversal observed in high dielectric constant media or in the presence of poorly accessible cations (e. g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation